Caracterização de asfaltenos e outros derivados do petróleo por ESI(±)FT-ICR MS - Pinto, Fernanda Endringer (2019)
Positive and negative ion-mode electrospray (ESI(±)) technique coupled to Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) preferably provides ionization of polar constituents with ultra-high resolution and mass accuracy. The purpose of this research was to characterize asphaltenes and vacuum gasoil (VGO) by ESI(±)FT-ICR MS. Three asphaltenes subfractions obtained from precipitation with different n-hexane/crude oil ratios (3.5V, 3.5–6V, and 6–40V), and three subfractions obtained from adsorption onto CaCO3 (non-adsorbed, adsorbed, and irreversibly adsorbed), besides the original asphaltenes were analyzed. With the data generated from the ESI(±), solubility parameters (δ) were calculated. ESI(±) data showed that polar compounds species with lower carbon numbers were mainly found for the irreversibly adsorbed subfraction, while the subfraction 6-40V presented a more aromatic profile than of remaining subfractions. The δ obtained from the ESI(+) results showed an overlapping of Nx species indicating that subfractions produced in n-hexane had a lower tendency to precipitate in hydrocarbons in relation to subfractions produced onto CaCO3. The last presented a shift to higher δ for both ionization modes ESI(±), indicating that the fractionation onto CaCO3 was able to produce more distinct subfractions, with different δ, aromaticity, and polarity. The VGO samples consisted of VGO original and VGO treated with clay and silica obtain from breakthrough curves on two temperature levels (80 and 150 °C) and different rupture times (from 60 to 420 min). ESI(±) analyses of GOV and their fractions indicated that the removal of nitrogen compounds by the clay adsorbent was enhanced when the temperature was higher (150 °C). Conversely, silica has shown a rich adsorption capacity at moderate temperatures (80 °C). This result corroborates the existence of two different adsorption mechanisms. The clay adsorption mechanism is likely a chemisorption process, while the silica adsorption mechanism is related to physisorption. Both processes displayed better performance in short rupture times, for example, at 60 min. Class distribution showed a preferential removal of N[H] and N2[H] compounds with low carbon numbers (< C26) for ESI(+). However, the ESI(−) data showed that, although adsorbents, such as clay, present acid sites and selectively adsorb basic nitrogen species, a great reduction of non-basic nitrogen species, such as carbazole and its analogues, is clearly observed mainly for VGO samples treated with clay at 150 °C and with silica at 80 and 150 °C. The application of ESI (±) FT-ICR MS in the analysis of petroleum and derivatives facilitated the specific comparison of compounds between the samples, due to the ability of the equipment to monitor thousands of species present in the oil, with a high precision and mass resolution, as well a promise tool in the determination of different reaction mechanisms.